Increasing gender diversity in organisations: What works? - Luciana Vieira (Journal of Applied Leadership and Management, 2022)
Research questions: Which practices were effectively implemented by organisations in Germany to promote and manage gender diversity and which key performance indicators (KPIs) did they implement to support gender diversity management? What is the maturity level of this implementation? Which practices for the promotion and management of gender diversity contributed more to advancing the participation of women in the workforce and in management? Methods: Empirical primary research and quantitative analysis were used to answer the research questions and test hypotheses. Data on the implementation of 22 diversity and inclusion (D&I) practices and 12 supporting KPIs to promote and manage gender diversity were collected through a survey with 139 D&I or human resources (HR) professionals and managers in large organisations in Germany that are publicly committed to D&I. Results: Practices to promote and manage gender diversity and supporting KPIs are widely used in the surveyed organisations. The maturity of the implementation is on intermediate to advanced levels. Organisations that reported an increase in the female workforce have more diversity practices and more maturity in the use of targeted recruitment and bias reduction in promotion decisions, as well as in the use of KPIs to monitor new hires and attrition rates by gender. Organisations where the proportion of women in management increased use more diversity practices, more supporting KPIs, and have higher maturity in the implementation of both. Particularly, these organisations are more mature in the use of women's networks, measures to raise the visibility of role models, diversity/anti-bias trainings and practices to manage diversity, such as D&I staff, D&I committees, and reporting mechanisms to the CEO. A correlation analysis showed that higher increases in the proportion of women in the workforce are associated with higher maturity in using gender- diverse interview teams.
Keywords: 650